Assessment of Natural Radionuclides and Some Toxic Metals in Vegetables Cultivated Around Ibese and Ewekoro Cement Industries in Ogun State, Southwest Nigeria - Augustine Kolapo, Ademola; Adeniyi, Adejumobi Caleb (Journal of Science and Technology, 2021)
Absorption of natural radionuclides and heavy metals (HM) contents from wastes is a possible way of soil contamination which subsequently adversely affects the plants cultivated in the area and human health when consumed. Therefore, this study aimed to measure NORMs and some toxic metals in five types of vegetable; Telfairia occidentalis, Corchorus olitorius, Solanum Lycopersicum, Amaranthus hybridus, and, Talinum fruticosum around two cement industries in Ogun state using Sodium Iodide detector and Atomic Absorption Spectrometer. The mean concentrations of radionuclide (226Ra, 228Ra, and 40K) in the samples were 21.31±2.40, 10.62±2.52 and 220.71±14.32, respectively in Telfairia occidentalis and lower in all other samples. The metals analyzed (Pb, Cd, Cu, Ni and Zn) have their average concentrations as 0.08, 0.18, 3.21, 0.45 and 2.15 mg kg-1 respectively in Telfairia occidentalis; 0.11, 0.07, 4.29, 0.58 and 2.84 mg kg-1 in Corchorus olitorius; 1.00, 0.18, 4.20, 0.34 and 3.60 mg kg-1 in Solanum Lycopersicum. The hazard indices obtained were 1.47, 1.69, 2.21, 1.71 and, 1.29, respectively, meaning hazard is probable from consuming the vegetables. The committed doses (0.4 and 0.38 µSv y-1) and the cancer risks (0.41 ×10-6 in Ibese and 0.37 × 10-6) estimated are well below the United Nation Scientific Committee on Energy and Atomic Research.